Differential Responses of Vanilla Accessions to Root Rot and Colonization by Fusarium oxysporum f. sp. radicis-vanillae - Koyyappurath, Sayuj; Conéjéro, Geneviève; Dijoux, Jean Bernard; Lapeyre-Montès, Fabienne; Jade, Katia; Chiroleu, Frédéric; Gatineau, Frédéric; Verdeil, Jean Luc; Besse, Pascale; Grisoni, Michel (Frontiers in Plant Science, 2015)
Root and stem rot (RSR) disease caused by Fusarium oxysporum f. sp. radicis-vanillae (Forv) is the most damaging disease of vanilla (Vanilla planifolia and V. ×tahitensis, Orchidaceae). Breeding programs aimed at developing resistant vanilla varieties are hampered by the scarcity of sources of resistance to RSR and insufficient knowledge about the histopathology of Forv. In this work we have i) identified new genetic resources resistant to RSR including V. planifolia inbreds and vanilla relatives, ii) thoroughly described the colonization pattern of Forv into selected vanilla accessions, confirming its necrotic non-vascular behavior in roots, and iii) evidenced the key role played by hypodermis, and particularly lignin deposition onto hypodermal cell walls, for resistance to Forv in two highly resistant vanilla accessions. Two hundred and fifty-four vanilla accessions were evaluated in the field under natural conditions of infection and in controlled conditions using in-vitro plants root-dip inoculated by the highly pathogenic isolate Fo072. For the 26 accessions evaluated in both conditions, a high correlation was observed between field evaluation and in-vitro assay. The root infection process and plant response of one susceptible and two resistant accessions challenged with Fo072 were studied using wide field and multiphoton microscopy. In susceptible V. planifolia, hyphae penetrated directly into the rhizodermis in the hairy root region then invaded the cortex through the passage cells where it induced plasmolysis, but never reached the vascular region. In the case of the resistant accessions, the penetration was stopped at the hypodermal layer. Anatomical and histochemical observations coupled with spectral analysis of the hypodermis suggested the role of lignin deposition in the resistance to Forv. The thickness of lignin constitutively deposited onto outer cell walls of hypodermis was highly correlated with the level of resistance for 21 accessions tested. The accumulation of p-coumaric and sinapic acids, two phenolic precursors of lignin, was observed in the resistant plants inoculated with Fo072, but not in the susceptible one. Altogether, our analyses enlightened the mechanisms at work in RSR resistant genotypes and should enhance the development of novel breeding strategies aimed at improving the genetic control of RSR of vanilla.